The struggle against corruption during the democratic transition: theorising the emergent role of CSOs - Chalmers, Ian; Setiyono, B. (Institute for Social Development & Policy Research, Seoul National University, 2012)
This article argues that civil society organisations (CSOs) play an increasingly prominent role in combating corruption in countries that have recently democratised. Democracy cannot survive without accountability, but in transitional democracies the formal accountability mechanisms associated with democratic governance are typically ineffective. “Horizontal accountability” in the form of check-and-balance mechanisms between various state institutions usually does not function well due to the poor capacity of state institutions. “Vertical accountability” through general elections very often fails to bring state actors to account. In such circumstances, we should not be surprised that corruption becomes endemic. In order to reduce corruption, therefore, emerging democracies need far-reaching political reforms to develop sound systems of accountability. But because many state and business actors represent groups with a vested interest in corrupt activities and which generally resist reform initiatives, this article proposes that initiatives for such reform are best generated by organisations based on political movements within the broader community, namely ‘civil society organisations’.